If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x+1)=3x-1
We simplify the equation to the form, which is simple to understand
-2(x+1)=3x-1
Reorder the terms in parentheses
+(-2x-2)=3x-1
Remove unnecessary parentheses
-2x-2=+3x-1
We move all terms containing x to the left and all other terms to the right.
-2x-3x=-1+2
We simplify left and right side of the equation.
-5x=+1
We divide both sides of the equation by -5 to get x.
x=-0.2
| y/8-5=-3 | | 6-7x=5x-9x-15 | | -4c-6c=-110 | | 9x^2-15=0 | | 54x-38=4x+90 | | 6x+7-2(x+1)=9X+7 | | (24a+56b)= | | 0.6(10.00)+0.8x=0.72(10.00+x) | | 0.5(2x+.75)-1/3(.01+x)=1 | | 5y=7.5 | | 3.5a=3.2(8) | | 4x+8y=-12 | | 17=p-3-39 | | 7x^2+34x-39=0 | | (5x+20)(3x-15)=0 | | 3x+4-x=2(x-4)+3 | | w-5=3 | | x+3x+7=x+28 | | 3x-9x=24 | | 4+m/3=12 | | n=1.2n-14 | | 2k=541/2+9 | | -(5a-3)-(5a-5)=16-(5a+3) | | 5x^2-18x=1225 | | 12z=38 | | 9x-9=-2+10x+12 | | 3x-8=2y+17 | | 23+h-9=12 | | 7x+6x-42=105-8x | | 3(4w-1)-5=10 | | -3/10=x-7/8 | | 9x-9=2+10x+12 |